Proposing a precision-enhancing method for sagittal plane alignment during total knee arthroplasty - Jisu Park; Hyeongyu Lim; Chong Bum Chang (BMC Musculoskeletal Disorders)
Abstract Background Achieving appropriate alignment after total knee arthroplasty (TKA) is crucial for long-term survival of implant but alignment in sagittal plane is relatively not well studied. The purpose of this study was to (1) propose the preoperative sagittal planning method of TKA using X-ray, (2) validate its accuracy and (3) find factors contributing to inaccurate sagittal placement of the component. Methods Ninety-three knees of 71 patients were prospectively reviewed. Preoperative sagittal planning for the femoral and tibial component was conducted using simple X-ray images. The postoperative X-ray taken six weeks after surgery was used to validate the proposed method. The angle between the reference line and the expected resection line before surgery was defined as the preoperative gamma angle for the femur and delta angle for the tibia. Postoperatively, the angle between the same reference line and the actual component was defined as the postoperative gamma and delta angles, respectively. The target angle range for the difference between the preoperative and postoperative gamma and delta angles was set as -2° to 2°. Demographic and radiologic factors between groups that fell within and outside the target angle range were compared. Results Total 75 cases (80.6%) met the target angle range of distal femur resection. Femoral component tended to be placed in more flexed position than planned. Anterior femoral notching was not observed in all cases. Total 89 cases (95.7%) met the target angle range of proximal tibia resection. No factors were associated with the increased difference in preoperative and postoperative femoral and tibial prosthesis placement in multiple regression. Conclusions The proposed sagittal planning method for TKA demonstrated an accuracy of 80.6% for the femoral component and 95.7% for the tibial component. Since this method does not require any programs and additional costs, it could be a good alternative in situations where robotic-assisted TKA is not available.